Procedures Noncompliance in Muslim Marriage Application: A Case Study in Syariah Courts in Terengganu, Malaysia - Asiah, Bidin; Kamaliah, Salleh; Akmal, Mohamad; Noraida, Harun; Noor Ashikin, Hamid (2018)
The Administration of Islamic Family Law Enactment in each state in Malaysia has laid down specific rules and procedures for the application of marriage. The Islamic Religious Affairs Department is the body to implement the rules and procedures. Despite of having the clear provisions on procedures, there are many cases of breach of those procedures. The objective of this article is to discuss the marriage procedures under the Administration of Islamic Family Law (Terengganu) Enactment 1985. Any noncompliance with the procedures will affect the registration of the marriage. Thus, the parties need to apply for confirmation of marriage in Syariah courts. This article will further highlight the cases that have been heard in Syariah Courts in Terengganu for confirmation of marriages. Lastly this article will discuss the implication of unregistered marriage to the married couple. The study was conducted based on the analysis of documents, namely the Administration of Islamic Family Law (Terengganu) Enactment 1985 (the Enactment) and data obtained from Terengganu Syariah courts.